Amoxicillin degradation at ppb levels by Fenton's oxidation using design of experiments - Vera Homem (2010)
A central composite factorial design methodology was employed to optimise the amoxicillin degradation using the Fenton s oxidation treatment In this study the variables considered for the process optimisation were the hydrogen peroxide and ferrous ion initial concentrations and the temperature for an antibiotic concentration of 450 mu g L-1 at pH = 3 5 This methodology also allowed assessing and identifying the effects of the different factors studied and their interactions in the process response An appropriate quadratic model was developed in order to plot the response surface and contour curves, which was used to perform the process optimisation From this study it was concluded that ferrous ion concentration and temperature were the variables that most influenced the response Under the optimal conditions (hydrogen peroxide concentration = 3 50-4.28 mg L-1 ferrous ion concentration = 254-350 mu g L-1 and temperature = 20-30 degrees C) it was possible to achieve total amoxicillin degradation after 30 min of reaction.